Future Orientation as a Mediator Between Career Adaptability and Life Satisfaction in University Students. (December 2018) - Cabras, Cristina; Mondo, Marina
Studies have emphasized that career adaptability and future orientation are important factors in one's ability to deal with difficulties and achieve life satisfaction. This study examines the relationships among future orientation, career adaptability resources, and life satisfaction. Survey data from 373 Italian and Spanish university students were analyzed using structural equation modeling. The results indicated that future orientation fully mediated the relationship between career adaptability and life satisfaction in the Italian and the Spanish students. These findings suggest that university students who are confident in their career adaptability are satisfied with life because they are confident about their future prospects. The implications of these observed relationships for counseling interventions and further research are discussed.